Synthesis, Characterization, Antimicrobial And In-Silico Predictions Of 5,6-Dihydropyrimidin-2(1H)-One And 4,5-Dihydro-1H-Pyrazole Derivatives (The Review of Diabetic Studies, 2025)
Two new chalcone-based derivatives produced using a simple condensation technique with starting compound 1 with phenylhydrazine (2) and urea (4) derivatives 3 and 5 are presented in the current work together with their design, synthesis, and biological evaluation. FTIR, 1H NMR, 13C NMR, and HRMS tests were employed to verify the structure. Against four bacterial strains Staphylococcus aureus, Escherichia coli, Bacillus subtilis and Pseudomonas aeruginosa and two fungal strains Trichoderma asperellum and Candida parapsilosis the synthesized chemicals were tested for antimicrobial activity. Derivative 5 showed significant antibacterial activity, having a 14 mm zone of inhibition against Staphylococcus aureus, 8 mm against E. coli, and 9 mm against P. aeruginosa, with no inhibition against B. subtilis. In antifungal tests at 1000 µM concentration, it showed inhibition zones of 9. 33 mm against T. asperellum and 9. 33 mm against C. parapsilosis. Derivative 3 showed mild activity with maximum inhibition zones of 8 mm (S. aureus, E. coli, P. aeruginosa) and 9. 66 mm (T. asperellum, C. parapsilosis) in comparison. In-silico ADMET profiling of both compounds, done with AdmetLab 3.0 and SwissADME instruments, revealed acceptable absorption, distribution, metabolism, excretion, and toxicity profiles similar to those of the standard drugs Amphotericin B and Ciprofloxacin. These findings show the potential of chalcone-based templates as possible antibacterial agents.